2014
DOI: 10.1186/1756-3305-7-228
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia detection in insects through LAMP: loop mediated isothermal amplification

Abstract: BackgroundThe bacterium Wolbachia is a promising agent for the biological control of vector-borne diseases as some strains have the ability to block the transmission of key human disease-causing pathogens. Fast, accurate and inexpensive methods of differentiating between infected and uninfected insects will be of critical importance as field-based trials of Wolbachia-based bio-control become increasingly common.FindingsWe have developed a specific and sensitive method of detecting Wolbachia based on the isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…The LAMP assay is a sensitive method for detecting low-abundance target DNA in a sample (Notomi et al, 2000). Goncalves Dda et al (2014) developed a LAMP assay for Wolbachia detection in insects (Goncalves Dda, Cassimiro, de Oliveira, Rodrigues, & Moreira, 2014). Recently, Bhadra et al (2018) reported a specific and sensitive assay that combines LAMP and oligonucleotide strand displacement (OSD) for detecting both species identity and Wolbachia .…”
Section: Resultsmentioning
confidence: 99%
“…The LAMP assay is a sensitive method for detecting low-abundance target DNA in a sample (Notomi et al, 2000). Goncalves Dda et al (2014) developed a LAMP assay for Wolbachia detection in insects (Goncalves Dda, Cassimiro, de Oliveira, Rodrigues, & Moreira, 2014). Recently, Bhadra et al (2018) reported a specific and sensitive assay that combines LAMP and oligonucleotide strand displacement (OSD) for detecting both species identity and Wolbachia .…”
Section: Resultsmentioning
confidence: 99%
“…Isothermal nucleic acid amplification assays would facilitate field-based vector monitoring, but most reported approaches rely on nucleic acid purification and non-specific readout, and thus suffer from laborious setup and the risk of false positives [6163]. Probe-read isothermal methods such as the recombinase polymerase assay (RPA) are more reliable but still require expensive and proprietary reaction formulations and probes, which limits their flexibility and versatility in assay engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Three LAMP assays have thus far been published for Wolbachia monitoring (16)(17)(18). Gonçalves et al (2014) targeted Wolbachia's 16S ribosomal protein sequence, and amplified Wolbachia across multiple strains, including wAlbB, wMel, and wMelPop. A study applying this assay to field samples in Malaysia found that it compared favourably with a standard PCR method for Wolbachia detection in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus mosquitoes, detecting a higher infected rate than observed with PCR (19). However, it should be noted that this study used an experimental design that did not include the loop primers, which Gonçalves et al (2014) consider essential to ensure specificity of the assay.…”
Section: Introductionmentioning
confidence: 99%